A NEW FACILE AND SENSITIVE METHOD FOR THE ESTIMATION OF TAPENTADOL (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
A simple, economical, precise, reliable and reproducible visible Spectrophotometric method has been developed for the estimation of Tapentadol in bulk as well as in tablet formulations. This method is based on the formation of Blood red colored chromogen with2, 2 -bipyridyl which shows maximum absorption at λ max 520 nm. The absorbance-concentration plot is linear over the range 50-250µg/mL. Results of analysis were validated statistically. Recovery studies were also performed. The proposed method is economical, accurate precise and sensitive for the estimation of Tapentadol in bulk drug and its formulation.